IgM libraries of 30 Swedish rheumatoid arthritis cases - Hardt, Uta; Corcoran, Martin; Narang, Sanjana; Malmström, Vivianne; Padyukov, Leonid; B. Karlsson Hedestam, Gunilla (Karolinska Institutet, 2022)
The data contains two paired-end read files as fastq.gz per individual library. The sequencing files are in a folder "1" in a folder of the individual labelled "RA_ID_IGM".

The libraries were made with an Immunoglobulin M reverse primer and a 5' mulitplex primer set binding in the leader region. The libraries were analyzed with IgDiscover in default settings.

Data Access Statement

The data can be made available for research purposes after publication. The human data has to remain stored in secure places with restricted access. Please send a request with your institutional affiliation, the purpose of the data request and data management information. Access will be granted by the main authors. If you are affiliated with a Swedish institution access is given through Uppmax.
Keywords: Immunogenetics (incl. genetic immunology); Medical and Health Sciences; Medicin och hälsovetenskap; Immunology; Immunologi